Suhu Makanan dan Sisa Makanan Pasien Dewasa Diet Lunak di Rawat Inap Penyakit Dalam Rumah Sakit Umum Daerah Kota Semarang - Najibah Nuraini; Sufiati Bintanah; Kartika Nugraheni (Jurnal Gizi, 2017)
The food temperature is one of the factors affecting the leftovers of soft diet inpatients of the hospital. Research aims to understand how the relationship of food temperature with leftovers of soft diet of internist inpatients.  The kind of research is explanatory reserch using survey methods and with the crosssectional approach. The populationis  all of adult inpatients who obtain the  diet soft at public hospital of Semarang City. The sample chosen by the inclusion and exclusive criteria that we have seted. Data analysis using the pearsoncorrelationstatistic test. The result shows from the number of 33 samples,  there are  54,4 % of them are 41-60 years old, 57,6 % a women, 60,6 % who hospitalized three days or above, 39,4 % who seniorhigh school educated and 42,4 % of them who suffer febris medical. The food’s temperature was4,5 o  C – 60 o  C, in danger zone. Leftover food of porridge diet was 22,15% ±SD 7,35%, animal protein diet was 34,14% ± SD9,30%, nabati protein diet was 38,63% ±SD 14,53% and vegetables diet was  38,10% ±SD 12,20%. There is no correlation between the food’s temperature with leftovers of porridge diet (p = 0.277, no correlation between the food’s temperature with leftovers of animal protein diet (p = 0,116),no correlation between the food’s temperature with leftovers of nabati protein diet (p = 0,709).  There is a correlation between thefood’s temperature with leftovers of vegetablesdiet(p = 0,006). The conclusion, at the hospital of Semarang City, especialy the adult inpatient, the food’s temperature related to the food’s rest of vegetable diet, but no related to the food’s rest of porridge diet, animal protein diet  and nabati protein diet. Keywords :Food Themperature, Leftovers, Soft Food